HIV surveillance in MENA: recent developments and results. (23rd February 2013) - Bozicevic, Ivana; Riedner, Gabriele; Calleja, Jesus Maria Garcia
Abstract : Objectives: To provide an overview of the current level of development and results from the national HIV surveillance systems of the 23 countries of the Middle East and North Africa (MENA), and to assess the quality of HIV surveillance systems in the period 2007–2011. Methods: A questionnaire was used to collect the information about the structure, activities and the results of HIV surveillance systems from the National AIDS Programmes. Assessment of the quality was based on four indicators: timeliness of data collection, appropriateness of populations under surveillance, consistency of the surveillance sites and groups measured over time, and coverage of the surveillance system. Results: Only in four countries did surveillance systems enable assessment of epidemic trends in the same populations and locations over time, such as in pregnant women (Morocco, Iran), injecting drug users (Iran, Pakistan), female sex workers (Djibouti, Morocco) and male sex workers (Pakistan). There is increasing evidence of HIV infection being firmly established in at least one of the populations most at risk of HIV in nine MENA countries, while lower risk populations show elevated HIV prevalence in South Sudan, Djibouti and some parts of Somalia. Conclusions: The performance of HIV surveillance systems in several of the MENA countries has improved in recent years. The extent of HIV epidemics in the populations most at risk of HIV is still largely unknown in 10 countries. Multiple data sources that most of the countries still lack would enable indirectly estimation not only of the patterns of HIV epidemics but also the effectiveness of HIV responses.